2016
DOI: 10.1120/jacmp.v17i6.6345
|View full text |Cite
|
Sign up to set email alerts
|

The dosimetric impact of control point spacing for sliding gap MLC fields

Abstract: Dynamic sliding gap multileaf collimator (MLC) fields are used to model MLC properties within the treatment planning system (TPS) for dynamic treatments. One of the key MLC properties in the Eclipse TPS is the dosimetric leaf gap (DLG) and precise determination of this parameter is paramount to ensuring accurate dose delivery. In this investigation, we report on how the spacing between control points (CPs) for sliding gap fields impacts the dose delivery, MLC positioning accuracy, and measurement of the DLG. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Despite the lower standard deviation of log files and the reasonable agreement with EPID in this study, it is not recommended to rely solely on log files as the readout is sourced directly from the linac control system. In particular, care should be taken when using log files for MLC QA as the positions recorded may not reflect the actual location of the MLCs as other authors have demonstrated . In this study the log file analysis appeared to be sensitive to delivery errors introduced into Dose Test 2 and MLC Test 1, however this is due to the fact that errors were introduced into the DICOM plan file rather than the MLC, gantry angle or dose calibration.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Despite the lower standard deviation of log files and the reasonable agreement with EPID in this study, it is not recommended to rely solely on log files as the readout is sourced directly from the linac control system. In particular, care should be taken when using log files for MLC QA as the positions recorded may not reflect the actual location of the MLCs as other authors have demonstrated . In this study the log file analysis appeared to be sensitive to delivery errors introduced into Dose Test 2 and MLC Test 1, however this is due to the fact that errors were introduced into the DICOM plan file rather than the MLC, gantry angle or dose calibration.…”
Section: Discussionmentioning
confidence: 76%
“…In particular, care should be taken when using log files for MLC QA as the positions recorded may not reflect the actual location of the MLCs as other authors have demonstrated. 16,23,24 In this study the log file analysis appeared to be sensitive to delivery errors introduced into Dose Test 2 and MLC Test 1, however this is due to the fact that errors were introduced into the DICOM plan file rather than the MLC, gantry angle or dose calibration. As the EPID measurements are a direct independent measurement of the MLC-defined radiation field and output they are not subject to the same inadequacies as log files and may be used as a gold standard for both MLC and dose delivery accuracy.…”
Section: H Machine Log File Analysismentioning
confidence: 72%
See 1 more Smart Citation
“…Retrospective assessment of MLC accuracy and dose evaluation has been previously performed using machine log files for conventional radiotherapy and MLC tracking 6,9,12,13,30,31 . While use of log files is efficient and convenient, several studies have shown that they may be insensitive to MLC errors and are not truly independent of the linac control system 32‐34 . Agnew et.…”
Section: Discussionmentioning
confidence: 99%
“…Zwan et. al 34 . showed that log files can be insensitive to errors introduced into the planned MLC positions prior to communication with the MLC controller.…”
Section: Discussionmentioning
confidence: 99%